2021
DOI: 10.2147/prbm.s333593
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive Leadership and Subordinates’ Pro-Social Rule Breaking in the Workplace: Mediating Role of Self-Efficacy and Moderating Role of Employee Relations Climate

Abstract: Purpose: Drawing on the Social Information Processing (SIP) theory, the study sought to examine the link between inclusive leadership and employees' pro-social rule-breaking (PSRB) behavior through the mediating effect of self-efficacy. The study also investigates the moderating role of employee relations climate between inclusive leadership and self-efficacy. Methods: The study's sample size consists of 438 full-time corporate employees at 47 organizations from China. Statistical analysis methods were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 71 publications
1
19
0
1
Order By: Relevance
“…The pandemic had engendered a conscious feeling of emotion (ie, fears and worry), posing unprecedented challenges to worldwide industries. 19 , 20 …”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…The pandemic had engendered a conscious feeling of emotion (ie, fears and worry), posing unprecedented challenges to worldwide industries. 19 , 20 …”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“… 27 , 28 Second, IL demonstrates treatment of fairness and justice via openness, availability, and accessibility when interacting with subordinates, which convinces employees that their organization is committed to involving all employees in the operation of the organization. 29 These positive interactive relationships inclusive leaders provide would bring together the final employees’ attitude and active behavior, such as voice, 18 innovation, 30 taking charge, 31 , 32 self-efficacy, 33 and creativity. 34…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Binary tenure refers to the period in which a follower had worked with his or her leader. Although some prior studies have shown that dyadic tenure has no significant effect on PSRB ( Zhu et al, 2018 ; Chen et al, 2019 ; He B. et al, 2021 ), we believe binary tenure might have a great impact on leader-member exchange and guanxi, which, in turn, influence employees’ psychological safety in engaging extra-role workplace behaviors ( Sparrowe and Liden, 2005 ; He et al, 2019 ). As such, we call for future research to control binary tenure in their studies regarding employee-supervisor dyads.…”
Section: Discussionmentioning
confidence: 57%